Coronary artery calcium and intima‐media thickness are associated with level of cytomegalovirus immunoglobulin G in HIV‐infected patients. Issue 1 (4th September 2018) - Knudsen, A; Kristoffersen, US; Panum, I; Hansen, YB; Skottrup, PD; Hasbak, P; Kjaer, A; Lebech, A‐M
Abstract : Abstract: Coinfection with cytomegalovirus (CMV) may be involved in cardiovascular disease in HIV‐infected patients. We found that higher level of CMV immunoglobulin G (IgG) was independently associated with an increased risk of coronary artery calcium and higher intima‐media thickness in HIV‐infected patients but not in healthy controls after adjustment for other cardiovascular risk factors and levels of herpes viridae IgG.